(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This paper addresses the modeling challenge for the Severny Mubarek field caused by limited legacy PVT data: in a number of archived reports, the reservoir gas composition is presented in an overly aggregated form (as a C5+ fraction), which leads to significant calculation errors in reservoir simulation software. Based on the proposed methodology, mathematical splitting of the heavy C5+ fraction into pseudocomponents was performed using the Whitson correlation, which relies on a three-parameter gamma distribution. Critical properties for each pseudocomponent were calculated using Pedersen correlations, followed by tuning of the Peng–Robinson equation of state. As a result, the model reproduces the dew-point pressure with high accuracy (99.6%, calculated value 242.9 bar vs. actual 243.9 bar), improving the reliability of gas and condensate production forecasts and supporting more robust field development planning.